THE WINDS OF CHANGE: HOW GOVERNMENT-LED PROGRAMS ARE TRANSFORMING THE ORANG ASLI COMMUNITY (Journal of Governance and Development (JGD), 2024)
The Orang Asli community, Orang Asli Malaysia, has long faced socioeconomic challenges due to being marginalized and isolated frommainstream society. However, the government’s efforts to implement socioeconomic development programs have brought significantpositive changes to their communities. This paper examines the impact of the government-led program on the Orang Asli community,particularly in settlement, economy, and social. This study focuses on the Organized Settlement Program, Economic Development Program and Social Development Program. This study uses data from government reports, academic publications, and interviewswith members of the Orang Asli community. Findings show that government-led programs have increased access to education, bettereconomic opportunities, and better health care services for Aboriginal people. The study also highlighted the challenges that remain in trying to fully address the socioeconomic gap the Orang Asli community faces. Overall, this paper provides insight into the transformative power of government-led programs in addressing the socioeconomic challenges faced by marginalized communities and the importance of continued efforts to promote equitable and sustainable development.